Heterogeneous consumers, vertical product differentiation and the rate of innovation - Josef Zweimüller; Johannes K. Brunner (Institute for Advanced Studies (IHS), 1996)
This paper studies the impact of income inequality on the level of innovative activities in a model where innovations result in quality improvements. The market for quality goods is characterized by a natural oligopoly with three types of consumers - rich, middle class and poor. In general, we find that for reasons of strategic price setting a more equal distribution of income is favourable for innovation incentives. This is consistent with empirical evidence suggesting that countries with a more equal distribution of income have grown faster.
Keywords: O31; L15; L16; D43; H23; 330; inequality; income distribution; heterogeneity; innovation; endogeneous growth; product quality; vertical product differentiation; Konsumentenverhalten; Produktdifferenzierung; Innovation; Theorie